PENGEMBANGAN KNOWLEDGE SISTEM PEMILIHAN BIBIT SAWIT MENGGUNAKAN PENDEKATAN USABILITY ENGINEERING DINAS PERKEBUNAN PROVINSI PAPUA - Surianti Surianti; Nur Ain Banyal (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : One way to guarantee the development of oil palm in Indonesia is to ensure the availability of superior and quality seeds. Besides that, the development of the oil palm plantation industry so far has not been fully followed by an adequate increase in the nursery industry, even though seedlings play an important role in increasing the productivity of palm oil in general. Data collection method used is observation. Observation is a technique to go directly to the field at the Papua Provincial Plantation Office. This study uses a usability engineering approach and knowledge management system life cycle (KMSLC) method. The results of this study are in the form of a palm oil seed knowledge management system in which data sources used also include book documents, journals especially those from oil palm research centers and provide consultations with oil palm experts. Error rates in this application are very low and few. Scores from each category are above average, meaning that usability in this system is good.